FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI BIDANG ADMINISTRASI KEPENDUDUKAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR - Raharjo, Welige Eko; Achnes, Sofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This writing is supposed to analysis the performance of the employees of population and civil registry office (DISDUKCAPIL) in Kampar regency. This essay is brought up based on performance problems of employees in involved instansion. The problems are about work quantity and quality. The results show that the work quantity still not optimal yet. It could be seen from work assessment, and the use in work time which is not enough to finish whole works on civil registry unit. Next, the quality of the employees which is not optimal yet, it could be seen from the target or purpose that is not reached yet, and the result of work is still not satisfying especially about birth certificate The concept of the theory is the theory that researchers use Hariandja performance: quantity of work, quality of work, job knowledge, teamwork and creativity. This study use squalitative research methods to study this deskriptif. In collecting the data, the researcher used the interview techniques, observation and documentation. By using key informanst as a source of information and as a source triangulation techniques in testing the validity of tha data. Key words: Employees performance analysis, DISDUKCAPIL